2008
DOI: 10.1016/j.juro.2008.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment With Finasteride Results in a Clinically Significant Reduction in Total Prostate Volume Compared to Placebo Over the Full Range of Baseline Prostate Sizes in Men Enrolled in the MTOPS Trial

Abstract: In this MTOPS data analysis long-term (more than 4 years) treatment with finasteride, either alone or in combination with doxazosin, led to a consistent, clinically significant reduction in total prostate volume compared to placebo in patients with lower urinary tract symptoms and benign prostatic hyperplasia whose baseline prostate size ranged from relatively small (less than 25 to 30 ml) to enlarged (40 ml or greater).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 3 publications
2
48
0
Order By: Relevance
“…22 Therefore, the progressive reduction of PV known to occur with 5ARI treatment may result in alleviation of BOO. 23 We hypothesize that it is the alleviation of the mechanical stress caused by BOO that then allows reversal of structural and functional changes in the bladder, thus leading to improvements in storage symptoms with a 5ARI of comparable magnitude to an a-blocker after 15 months of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…22 Therefore, the progressive reduction of PV known to occur with 5ARI treatment may result in alleviation of BOO. 23 We hypothesize that it is the alleviation of the mechanical stress caused by BOO that then allows reversal of structural and functional changes in the bladder, thus leading to improvements in storage symptoms with a 5ARI of comparable magnitude to an a-blocker after 15 months of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using TRUS found that 5ARIs reduce total prostate volume by 17%-46% and transition zone volume by 7%-25% within the first year of therapy (10)(11)(12). While total prostate volume and transition zone volume dynamics in response to 5ARIs are widely accepted, there have been conflicting reports regarding the effects of 5ARIs on peripheral zone volume.…”
Section: Role Of Prostatic Volume Determination In Bph Managementmentioning
confidence: 99%
“…Further secondary analysis suggested that the addition of finasteride was more effective in men with larger (>40 cm 3 ) prostates, as found in the PLESS, but the PREDICT trial was not designed to take this parameter into account [14]. Analysis of the longer MTOPS trial concluded that finasteride alone or in combination with doxazosin consistently resulted in clinically significant TPV reduction regardless of baseline prostate size [19][20][21]. There is still some debate as to the value of using combination therapy and adding a 5ARI in patients with smaller prostates, as opposed to the use of an alpha-blocker alone.…”
Section: Aris In the Treatment Of Bphmentioning
confidence: 99%